An in silico reverse vaccinology study of Brachyspira pilosicoli, the causative organism of intestinal spirochaetosis, to identify putative vaccine candidates. (November 2022) - Christodoulides, Myron; de Oliveira, Daysiane; Cleary, David W.; Humbert, Maria Victoria; Machado-de-Ávila, Ricardo A.; La Ragione, Roberto M.
Abstract: Brachyspira pilosicoli is a zoonotic bacterium that can cause intestinal spirochaetosis (IS) in avian species (AIS), pigs (PIS) and humans (HIS). In the absence of vaccines to prevent infections, we used genome-based reverse vaccinology (RV) to identify putative B. pilosicoli vaccine candidates. Genome sequence of B. pilosicoli strain B2904, an AIS isolate, was analysed with PSORTb3, CELLO, SOSUIGramN, LipoP, SignalP-5.0, TMHMM, BLAST 2.12.0 + , PDB database, SEED Viewer, eggNOG-mapper, UniProt, VaxiJen and Vaxign2, and Tblastn to generate a RV list of putative vaccine candidates. We also generated a linear B-cell chimera antigen using Blast-p, Emini Surface Accessibility Prediction, ABCpred, Expasy ProtParam and PepCalc programs. RV defined a list of 162 proteins containing 48 Outer Membrane (OM), 27 OM/Extracellular, 27 Extracellular, 4 Periplasm, 2 Surface, 2 Cytoplasm and 52 Unknown proteins. The list was characterised by an abundance of SPII lipoproteins. We found that genes encoding amino acid sequences of 146/162 (90%) proteins were present in 19 other B. pilosicoli genomes. A linear B-cell chimera antigen was generated from the amino acid sequences of 18 OM and Extracellular proteins. Our contemporary RV study represents a starting point for a comprehensive vaccine development strategy for preventing intestinal spirochaetosis. Graphical Abstract: Brachyspira pilosicoli reverse vaccinology ga1 Highlights: No vaccines are licensed for preventing intestinal spirochaetosis caused by Brachyspira pilosicoli. We identified candidate vaccine antigens using in silico reverse vaccinology. We developed a B-cell chimera antigen from linear epitopes of 18 outer membrane and extracellular proteins.